Aktivitas Antibakteri Ekstrak Etanol Daun Pepaya (Carica papaya Linn.) Terhadap Bakteri Pseudomonas aeruginosa - Nasri Nasri; Vera Estefania Kaban; Kasta Gurning; Hariyadi Dharmawan Syahputra; Denny Satria (Yayasan Literasi Sains Indonesia, 2022)
Pseudomonas aeruginosa is a Gram-negative bacterium that can cause nosocomial infections. The use of antibiotics in the treatment of non-adherent P. aeruginosa infections increases the risk of antibiotic resistance. Efforts to find new antibiotic compounds from plants continue to be carried out. Papaya leaves are widely spread among the public, which are often used as ingredients for vegetables and have antibacterial potential because they contain papain enzymes and a class of flavonoid compounds. The purpose of this study was to analyze the antibacterial activity of the ethanol extract of papaya leaves (Carica papaya Linn.) against P. aeruginosa by finding the value of the Minimum Inhibitory Concentration (MIC) and calculating the index activity value against the positive control. The method used in this research is Kirby-Bauer (disc diffusion method) with several variations of the test concentration. The results showed that the diameter of the inhibition zone at a concentration of 500 mg/mL was in the strong category with an inhibition zone diameter of 10.87 ± 0.06 mm. MIC at a concentration of 3.125 mg/mL. The index activity value was greatest at a concentration of 500 mg/mL with a value of 0.668. So it can be concluded that the ethanol extract of papaya leaves (Carica papaya Linn.) has inhibitory activity against Pseudomonas aeruginosa.